A CROSS SECTIONAL SURVEY TO ANALYZE MUTRASHMARI NIDANA (AYUSHDHARA, 2016)
In the present study an effort was made to assess the Nidana and to analyze which of them are more susceptible to Mutrashmari in present era. The knowledge of Nidana is helpful for the proper diagnosis, prevention of disease and treatment also. The physician who is having proper knowledge of Hetu (Nidana) means to cure the disease and their proper utilization. 'Nidana Parivarjana' is the main method of keeping oneself free from the disease. This will help the individual to take care of diet and lifestyle. Questionnaire was prepared by included Ahara and Vihara which were mentioned under Nidana and Apathya for Ashmari. 100 Diagnosed cases of Mutrashmari from OPD and IPD of SDMCAH, Hassan, were taken for the study. In this present study occupation wise  majority of subjects were farmers (32.00%), Housewives (11.00%), Business Persons (12.00%). In results the order of majority of  Nidhanas like Snigdha Ahara (79%) Ruksha Ahara (76.0%), Chicken (74%), Madhura Ahara (60.0%), Long distance walking (73%) and Apathyas like Amla Rasa Sevana (75%), less intake of water (